Printed materials design to promote tourism for the modern Chinatown / Khwanchai Sukkon and Wiroj Klaeoklahan - Sukkon, Khwanchai; Klaeoklahan, Wiroj (2019)
This research "Printed materials design to promote tourism for the modern Chinatown" aims to find the identity of Chinatown use to design guidelines to present the information and to publicize the Yaowarat community. Yoawarat or Chinatown is the area in Bangkok that has Chinese residents settled when Bangkok was established, and it is considered as the largest Chinese-Thai population in Thailand. As a result, Yaowarat is a tourist attraction that is known to both Thais and foreigners. This research is conducted by collecting data with questionnaires from the tourists who are the new generation, 100 people aged between 21-35 years old and interview five graphic designers. The research results from data collection of tourists' opinions showed that: 1) Street Food is the highlight of the Chinatown area. 2) Red is the color that tourists think about Yaowarat. 3) Painting and drawing type of illustration attract tourists most. Research design results: 1) The Color: Warm tone colors and mostly red color. 2) Manuscript Grid is the most appropriate for the design 3.) San-serif Font is the most suitable for the headline 4) Serif Font is the most ideal for the text.